States Affected by Sea-Level Rise and Climate Displacement: Challenges for International Law and Human Rights - Hazyar Arumbinang, Mohammad; Yusuf Kohar, Halilintar (JUSTITIA JURNAL HUKUM, 2025)
This study investigates the legal obstacles related to sovereignty, climate-induced displacement, and human rights, emphasizing deficiencies in current international legal frameworks. This research offers a complete legal analysis of climate displacement and statehood loss, highlighting their interdependence, unlike earlier studies that have examined these topics independently. It also examines various legal remedies, including enhanced refugee rights, international acknowledgment of climate-displaced individuals, and novel legal frameworks for stateless communities. Rising sea levels provide unparalleled legal and humanitarian concerns, especially for low-lying island states confronted with the risk of inundation. As these governments progressively diminish in area, inquiries emerge about their legal legitimacy, sovereignty, and the entitlements of their displaced inhabitants under international law. Existing legal frameworks, such as the Montevideo Convention on statehood, the 1951 Refugee Convention, and international human rights treaties, provide inadequate protection for governments impacted by sea-level rise and their displaced populations. The study utilizes a normative legal framework, examining principles and norms of international law, and adopts a case study technique to qualitatively investigate the legal intricacies of the case. The results find that international law fails to address climate-induced displacement and statehood loss. It calls for recognizing deterritorialized statehood, expanding refugee protections, and establishing binding resettlement obligations to prevent statelessness and uphold human rights.